Penanggulangan Stunting Melalui Program SOTH (Sekolah Orang Tua Hebat) di Kota Malang - Aldi, Bintang; Najah, Savinatun; Hayat, Hayat (Idarotuna : Journal of Administrative Science, 2024)
In Indonesia, especially the city of Malang, stunting a chronic nutritional issue in children under five is a major concern. By educating catin (bride candidates) and educating parents on the best ways to care for their children, the SOTH program (Sekolah Orang Tua Hebat) aims to address the issue of stunting in Malang. The purpose of this study is to evaluate how well the SOTH program has worked to lower the prevalence of stunting in five Malang City subdistricts. Using a library approach method and quantitative research, this study collects secondary data from documents, literature, and statutory rules. According to the study's findings, stunting rates have decreased in the Malang metropolitan area.